Practices of scalecraft and the reassembling of political boundaries: the contested nature of national schooling reform in the Australian federation. (3rd September 2022) - Savage, Glenn C.; Di Gregorio, Elisa; Lingard, Bob
ABSTRACT: This article contributes new insights to research on the socio-spatial dynamics of policy production by synthesizing the concepts of "policy assemblage" and "scalecraft". By conceptualizing scale as socially-crafted rather than pre-existing (a priori), we argue that assemblage and scalecraft provide generative means for examining how scale is imagined and assembled, and the boundary dynamics associated with these processes. To make this argument, we focus empirically on changes to the governance of schooling policy in the Australian federation over the past two decades. We argue that despite being a federation in which subnational (state and territory) governments maintain responsibility for schools, a new national policy assemblage has emerged that rests upon and produces new forms of boundary imagining, crossing and blurring. This is generating tensions and issues for policy actors, central to which is contestation about federal involvement in national reform. Drawing upon insights from semi-structured interviews with senior policy actors, we argue that new ways of imagining and seeking to govern schooling, at the national scale, grate uncomfortably against the realpolitik of Australian federalism, the principles underpinning the design of federal systems, and forms of scalar thinking that shape how policy actors perceive the "ideal" division of roles and responsibilities.